Physical Health Versus Mental Health in Haemodialysis Patient: Assessment of Health-Related Quality of Life- A Single Centre Experience (Bangladesh Journal of Medical Science, 2022)
Objectives: Assessment of health related quality of life (HRQOL) is an essential part of evaluation of end stage renal disease (ESRD) as we have conducted this study on haemodialysis patients to see the HRQOL and to asses and compare the parameters which influence physical and mental health.Materials and Methods: This was a single centre study on haemodialysis patients using Short Form 36 (SF-36) of Kidney Disease Quality of Life (KDQOL). All the eight domains of HRQOL were assessed individually as well as summary scores for mental health (MCS Mental composite summary) and physical health (PCS Physical composite summary) were also evaluated. The questionnaire was completed by patient themselves and the clinical data was extracted from the medical records with prior consent from the patient.Results and discussion: The study participants showed a female predominance of 66% with a lower PCS and MCS scores among female participants in comparison to their male counterparts. Overall summary scores showed a lower PCS (38.71±8.15) than MCS (42.79±11.6) which reflects better mental health than physical health in the study population. A multiple regression analysis showed, the presence of residual renal function (β= -0.421, p= 0.02), duration of dialysis (β= 0.405, p= 0.03) and haemoglobin less than 12g/dL (β= 0.379, p= 0.02) were significant predictors of MCS.Conclusion: HRQOL in haemodialysis patients are influenced by socio-demographic as well as clinical parameters. In our population, kidney disease affects physical health more than mental health and the reasons are multifactorial.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 90-95